Increased Knowledge of Pringwulung Youth Group, Sleman, on the Use of Solar Energy to Support Energy Security - Abdul Haris Subarjo; Benedictus Mardwianta; Nurfi Ahmadi (Institute for Research and Community Services, 2020)
The youth group RT10/ RW40 Pringwulung, Condong Catur, Depok, Sleman Yogyakarta Special Region is located east of SMKN 2 Depok, Sleman. This youth group formed a semi-autonomous activity centre under the youth organization which aims to provide knowledge to children in RT 10 about natural science. To implement the objectives, the workshop collaborated with several partners as resource persons for the activity. Some of the partners included lecturers and student associations around the location. The educational background of the youth groups varies from high school to tertiary education. The Adisutjipto College of Technology through its lecturers attempted to increase the knowledge of youth group members through a community-service partnership program on alternative energy, especially solar energy which has the potential to support energy security. It is hoped that through this activity the youth groups would be able to increase their knowledge. This community-service activity used the presentation method and to check the knowledge of youth group members, tests or questions and answers were provided with both at the beginning of the activity and the end of the activity. In addition, a small group discussion (SGD) was also conducted so that the participants could discuss the presentation material and improve the understanding of the material. In this community service activity, there was an increase in participants' knowledge, and indicators of improvement were shown from the results of the small group discussion, pre-test, and post-test sessions. The average percentage of increase of their knowledge from the pre-test and posttest results was 36%.